The significance of criminological pre-sentence evaluation reports for rehabilitation directives in custodial settings: sex offender docket analysis - Hesselink, Annika W. (Acta criminologica, 2017)
Criminological pre-sentence evaluation reports assist courts by providing a comprehensive picture of an offender as a human being; the factors that contributed to the crime; an explanation of the offending behaviour, and also by recommending individualised sentencing options. In corrections, criminologists compile expert needs and risk assessments to determine exclusive pointers for offender rehabilitation efforts. It is thus assumed that criminological pre-sentence evaluation reports, that are compiled before sentencing, should form, to some extent, the basis of the criminological after-sentencing (offender needs and risk) reports. If this is the case, offenderspecific and offence-specific factors, as outlined in the pre-sentence reports, can guide correctional criminologists with the identification of offenders’ unique needs and risks for rehabilitation submissions. This article draws attention to the plausible worth that criminological pre-sentence reports hold for corrections. The aim is to establish if pre-sentence evaluation reports hold any benefit or significance for the exposure of rehabilitation indicators in terms of offender needs and risks. Four pre-sentence evaluation reports (document analysis) of adult sex offenders, who committed the same type of offence, with the same category victim, were assessed to ascertain the implication of the content of the reports for rehabilitation purposes. The researchers followed a qualitative approach to analyse and assess the case studies presented in the reports. Rehabilitation indicators in the reports were deliberated on and evaluated against what is scientifically known to be applicable and effective for rehabilitation of this type of sex offender. The findings indicate a void in correctional treatment targets (causes, motives, contributory factors, influences, triggers, and high-risk situations) and a vacuum in an offender-specific and offence-specific analysis. Aforementioned focus areas will contribute towards correctional criminologists’ assessments in underlying rehabilitation directives for the adequate rehabilitation and treatment of offenders.